2016
DOI: 10.1007/s12583-016-0677-3
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of highly fractionated I-type granites from Fengshun complex: Implications to tectonic evolutions of South China

Abstract: The South China Block is characterized by the large-scale emplacement of felsic magmas and giant ore deposits during the Yanshanian. We present zircon Hf isotopic compositions, whole-rock major and trace element compositions of the Fengshun complex, located in eastern Guangdong Province, South China. The Fengshun complex is a multi-stage magmatic intrusion. It is composed of two main units, i.e., the Mantoushan (MTS) syeno-monzogranites, alkali feldspar granites and the Hulutian (HLT) alkali feldspar granites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…The zircons in the rhyolites have negative ε Hf( t ) values ranging from −9.7 to −6.3 and yield two‐stage Hf model ages of 1,054–1,202 and 2,527–2,205 Ma. These Hf isotope characteristics are similar to those of Late Jurassic (164–145 Ma) magmatic rocks and felsic volcanic rocks in central‐eastern Fujian and eastern Guangdong (Figure 8 and Table 5; Guo et al, 2012; Liang et al, 2013; Liu et al, 2015; Qiu, Li, et al, 2017; Qiu, Yan, et al, 2017; Ye et al, 2014; Zhou et al, 2016). Furthermore, the Hf isotope data plot beneath or slightly above the chondrite line and above the domain of Cathaysia crustal basement rocks (Figure 8a), suggesting that the magma was derived from a crustal source.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The zircons in the rhyolites have negative ε Hf( t ) values ranging from −9.7 to −6.3 and yield two‐stage Hf model ages of 1,054–1,202 and 2,527–2,205 Ma. These Hf isotope characteristics are similar to those of Late Jurassic (164–145 Ma) magmatic rocks and felsic volcanic rocks in central‐eastern Fujian and eastern Guangdong (Figure 8 and Table 5; Guo et al, 2012; Liang et al, 2013; Liu et al, 2015; Qiu, Li, et al, 2017; Qiu, Yan, et al, 2017; Ye et al, 2014; Zhou et al, 2016). Furthermore, the Hf isotope data plot beneath or slightly above the chondrite line and above the domain of Cathaysia crustal basement rocks (Figure 8a), suggesting that the magma was derived from a crustal source.…”
Section: Discussionsupporting
confidence: 65%
“…The Dongyang dacitic crystal tuff has negative ε Hf( t ) values (−11.2 to −5.3) and two‐stage model ages of 2,650–2,121 Ma, which are similar to those of the Late Jurassic magmatic rocks in the surrounding areas and eastern Guangdong. Most of the data points are located close to the chondritic line and within or above the field of Cathaysia basement rocks, suggesting partial melting of crustal sources (Figure 8a; Table 5; Guo et al, 2012; Liang et al, 2013; Liu et al, 2015; Zhang et al, 2015; Zhou et al, 2015, 2016). Since the Dongyang dacitic crystal tuff lava is strongly peraluminous (Figure 6c), Palaeoproterozoic felsic rocks (meta‐igneous or metasedimentary rocks; Figures 3 and 4g) are possible magma sources.…”
Section: Discussionmentioning
confidence: 97%
“…It stimulated regional extrusion orogeny, with substantial crustal thickening and crustal temperature growth. However, as the subduction angle of the Palaeo‐Pacific Plate increased (Zhou et al, 2016), the lithosphere was fully extended and thinned. Mid‐crustal materials form acidic magma under conditions of decompression and melting.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of the deep dynamics, magmatism and metallogenic mechanism in South China mostly came from petrology and geochemistry (Chen & Xing, 2013; Hu & Zhou, 2012; Mao et al, 2014; Meng et al, 2012; Wang et al, 2011; Zhou et al, 2016). It is also of great significance to understand the deep metallogenic background by using geophysical techniques to image the deep structure of ore‐forming element‐rich areas at multiple scales and deducing the major geological events in the past in combination with geological chronology.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, we place identified uplift and exhumation events in the context of regional tectonics (Braun, ), thus deciphering the major orogenic pulses in the northeastern Chinese section of the Asian continental margin. Recent tectonic studies of different plate regions have shown that plate boundary stresses exerted a primary control upon coeval deformation and exhumation in intraplate settings (Allen & Davies, ; Echaurren et al, ; Fairhead et al, ; Gleadow et al, ; Holford et al, ; Lin et al, ; Shi et al, ; X. Zhang et al, ; Zhou et al, ). Therefore, in the final step of this study, we correlate the timing of orogenic and exhumation pulses in the Songliao Block and adjacent areas with major subduction and collision events along the Pacific and Neo‐Tethys (India‐Asia) plate boundaries of the continent.…”
Section: Introductionmentioning
confidence: 99%